Computational and experimental study of low energy Ar+bombardment on Nafion - Janchai Yana (2018)
Nafion, a polymer electrolyte membrane of a fuel cell, can be modified by low energy Ar+beam bombardment to increase its interfacial area with a catalyst. Recent experiments indicated that the sputtered sulfonate could lead to a decrease of hydrophilicity of Nafion when bombarded by a low energy Ar+beam. To investigate the surface modification at the atomic level, molecular dynamic (MD) simulations and experiment were carried out. The effects of Ar+at 0.5-3.0keV, and doses in the range of 1014-1015ionscm-2on the damage of the Nafion surface after bombardment were deduced from the simulations. This was assessed through both the chemical and physical changes of the Nafion side chain. The potential dissociation of the CS bond after bombardment was analyzed in terms of the elongated bond population. The percentage of the extended CS bond in the system was calculated to determine the possibility of sulfonate sputtering. Real-time determination of the amount of molecular species defragged under Ar+ion bombardment by quadrupole mass spectroscopy (QMS) was used. The percentage of the amount of potentially broken CS bonds after bombardment derived from MD simulations was found in a correlation with sputtering of SO3-fragments obtained from the experiments. The calculated results confirm the thresholds at 2.0keV as observed in experiment. © 2012 Elsevier B.V.